2020
DOI: 10.1007/s10118-021-2523-1
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and Dynamical Evolution of Block Copolymers in Shear Flow

Abstract: Conformation and dynamical evolution of block copolymers in shear flow is an important topic in polymer physics that underscores the forming process of various materials. We explored deformation and dynamics of copolymers composed of rigid or flexible blocks in simple shear flow by employing multiparticle collision dynamics integrated with molecular dynamics simulations. We found that compared with the proportion between rigid and flexible blocks, the type of the central blocks plays more important role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…As shown in Figure , for both interfacial copolymers in ternary blends and their homopolymer counterparts in homogeneous melts, P (( R e 2 ) 1/2 ) is a Gaussian distribution with the peak centered at the ensemble-averaged value of ⟨ R e 2 ⟩ 1/2 (as denoted by the dashed lines) at equilibrium but becomes a wide non-Gaussian bimodal distribution with the first peak at ( R e 2 ) 1/2 smaller than the equilibrium value and the second one at ( R e 2 ) 1/2 larger than the equilibrium value at γ̇ ≥ 1 × 10 –4 τ –1 for copolymers with χ C–D = 0.07 and homopolymers, γ̇ ≥ 3 × 10 –4 τ –1 for copolymers with χ C–D = 0.14 and γ̇ ≥ 3 × 10 –3 τ –1 for copolymers with χ C–D = 0.23. It has been well established that in (semi)­dilute polymer solutions and pure polymer melts, the broadenings of P (( R e 2 ) 1/2 ) with two peaks arise from the stretched-coil transition of individual chains under the fast, steady shear field. ,,, According to the recent evidence from simulations of monodisperse polymer melts, the flow-induced disentanglement of polymer chains leads to the onset of the stretched-coil transition via retraction or tumbling motion of individual molecules. For interfacial copolymer chains, however, the shear rate at the onset of the stretched-coil transition increases and noticeably exceeds that at the onset of the flow-induced disentanglement of interfacial copolymers with the increase of χ C – D . Intriguingly, unlike the homopolymer chains in homogeneous melts, the wide distribution of ( R e 2 ) 1/2 for interfacial copolymers becomes more asymmetrical as χ C–D increases, i.e., the stretched configuration (the second peak) takes a higher probability while the highly collapsed configuration (the first peak) possesses a lower probability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure , for both interfacial copolymers in ternary blends and their homopolymer counterparts in homogeneous melts, P (( R e 2 ) 1/2 ) is a Gaussian distribution with the peak centered at the ensemble-averaged value of ⟨ R e 2 ⟩ 1/2 (as denoted by the dashed lines) at equilibrium but becomes a wide non-Gaussian bimodal distribution with the first peak at ( R e 2 ) 1/2 smaller than the equilibrium value and the second one at ( R e 2 ) 1/2 larger than the equilibrium value at γ̇ ≥ 1 × 10 –4 τ –1 for copolymers with χ C–D = 0.07 and homopolymers, γ̇ ≥ 3 × 10 –4 τ –1 for copolymers with χ C–D = 0.14 and γ̇ ≥ 3 × 10 –3 τ –1 for copolymers with χ C–D = 0.23. It has been well established that in (semi)­dilute polymer solutions and pure polymer melts, the broadenings of P (( R e 2 ) 1/2 ) with two peaks arise from the stretched-coil transition of individual chains under the fast, steady shear field. ,,, According to the recent evidence from simulations of monodisperse polymer melts, the flow-induced disentanglement of polymer chains leads to the onset of the stretched-coil transition via retraction or tumbling motion of individual molecules. For interfacial copolymer chains, however, the shear rate at the onset of the stretched-coil transition increases and noticeably exceeds that at the onset of the flow-induced disentanglement of interfacial copolymers with the increase of χ C – D . Intriguingly, unlike the homopolymer chains in homogeneous melts, the wide distribution of ( R e 2 ) 1/2 for interfacial copolymers becomes more asymmetrical as χ C–D increases, i.e., the stretched configuration (the second peak) takes a higher probability while the highly collapsed configuration (the first peak) possesses a lower probability.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the conformational dynamics of individual polymer chains in a shear flow, most of the relevant works focused on (semi)­dilute polymer solutions. ,, It was only recently reported that athermal copolymers composed of rigid or flexible blocks tumble when the shear rate is larger than the reciprocal of the longest relaxation time, and the complete cycle of tumbling dynamics consists of four steps: stretching, aligning, flipping, and collapsing, which is the same as that of a single homopolymer chain in (semi)­dilute solutions or melts. ,, In the confined system, the constraints of the chain movement space will make single-chain dynamics different from those in the bulk phase. , For example, the tumbling motion of the polymer-solid interfacial chain is chaotic, and the hairpin-like (folded) configuration is dominant under strong shear flow. , For the system involving diblock copolymers segregated at interfaces between two immiscible homopolymers, the vertical interfacial movement to the interface of every copolymer is almost forbidden by the repulsive force between its blocks and the incompatible phases so that the interfaces in such systems can act as a “soft” wall . The presence of the “soft” wall is expected to influence the conformation response of individual interfacial copolymer chains and induce distinctive molecular mechanisms for tumbling motion from those chains in the bulk systems or interfacial homopolymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have revealed that vesicles can perform various motions in shear flow depending on the shear rate and viscosity ratio, including tank treading, tumbling, vacillating-breathing, and other motions. [21,22] Unlike the shear flow, Poiseuille flow is predominant in biological flows and microfluidics, in which the vesicles can perform unique behaviors. [23][24][25][26][27][28] Pommella et al studied the dynamic behavior of multilamellar vesicles (MLVs) under Poiseuille flow.…”
Section: Doi: 101002/mats202200027mentioning
confidence: 99%
“…[21][22][23][24][25] The lamellar alignment of the block copolymer under shear has also been examined in computational studies, many of which have used coarse-grained molecular dynamics (CGMD) to simulate block copolymer melts. [26][27][28][29][30][31][32] While using CGMD reduces the computational cost of block copolymer melts compared to all-atom molecular dynamics, it still captures the local conformation of chains and the microphase separation of the block copolymer. To apply a shear condition to molecular dynamics (MD), two shear methods with nonequilibrium conditions have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…To apply a shear condition to molecular dynamics (MD), two shear methods with nonequilibrium conditions have been suggested. For the shear acting on a bulk, the anisotropic box deformation method has been employed with the Lees-Edwards boundary condition and SLLOD algorithm, [26][27][28][29] while for a thin film, fixed lattice particles with a constant velocity have been used. 26,[30][31][32] Simple systems such as AB diblock copolymer melts have been studied under both shear conditions.…”
Section: Introductionmentioning
confidence: 99%